2019
DOI: 10.3390/ijms20112799
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging of Retinoid Cation Radicals by Urate, Trolox, and α-, β-, γ-, and δ-Tocopherols

Abstract: Retinoids are present in human tissues exposed to light and under increased risk of oxidative stress, such as the retina and skin. Retinoid cation radicals can be formed as a result of the interaction between retinoids and other radicals or photoexcitation with light. It has been shown that such semi-oxidized retinoids can oxidize certain amino acids and proteins, and that α-tocopherol can scavenge the cation radicals of retinol and retinoic acid. The aim of this study was to determine (i) whether β-, γ-, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…In several model systems it was also demonstrated that antioxidant protection increased synergistically when combination of carotenoids and vitamin E was used [28][29][30]. Importantly, carotenoids are among the most efficient quenchers of singlet oxygen, while vitamin E is an efficient scavenger of peroxyl radicals [31][32][33][34]. Synergistic protection by zeaxanthin and vitamin E against photic stress in ARPE-19 cells, mediated by photosensitizing dyes [35], lipofuscin granules [13], or melanosomes [36], was shown in our previous studies.…”
Section: Introductionmentioning
confidence: 68%
“…In several model systems it was also demonstrated that antioxidant protection increased synergistically when combination of carotenoids and vitamin E was used [28][29][30]. Importantly, carotenoids are among the most efficient quenchers of singlet oxygen, while vitamin E is an efficient scavenger of peroxyl radicals [31][32][33][34]. Synergistic protection by zeaxanthin and vitamin E against photic stress in ARPE-19 cells, mediated by photosensitizing dyes [35], lipofuscin granules [13], or melanosomes [36], was shown in our previous studies.…”
Section: Introductionmentioning
confidence: 68%
“…Under photo-oxidative conditions, heme oxygenase 1 is upregulated and catalyzes the production of ferrous iron and carbon monoxide, which may exacerbate cellular injury and oxidative stress by generating free radicals [30], further enhancing the vulnerability of the retina to oxidative stress and suggesting a feed-forward cycle of photo-oxidative stress-induced damage [30]. High antioxidant content in the retina (e.g., GSH, vitamin E and C, and macular carotenoids) may counteract light-induced oxidative damage [135][136][137]. Interestingly, intracellular iron triggers the regulatory effect of glutamate synthesis and secretion in RPE cells through its effects on cytosolic aconitase activity [138][139][140].…”
Section: Iron Causes Oxidative Stress and Lipid Peroxidation In The Retinamentioning
confidence: 99%
“…Alpha-tocopherol is a well-known free radical scavenger that can effectively inhibit lipid peroxidation, acting as a chain-breaking antioxidant [ 49 ]. It can also reduce semi-oxidized lutein, zeaxanthin and ATR to their original states [ 42 , 43 , 46 , 50 ]. Alpha-tocopherol is the main tocopherol present in human tissues, including the retina [ 38 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of interaction with singlet oxygen, hydrogen peroxide is formed, and ascorbate is oxidized to dehydroascorbate. Ascorbate can scavenge free radicals, including tocopheroxyl radical, and carotenoid and retinoid radical cations, thereby restoring these lipophilic antioxidants to the original state [ 42 , 43 , 46 , 49 , 50 , 62 ]. However, ascorbate can exert pro-oxidant effects in the presence of redox active metal ions such as iron by reducing these metal ions and thereby enabling them to function as catalysts of the Fenton reaction, where the reduced metal ion decomposes the hydrogen peroxide, leading to the formation of the most reactive free radical—the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 99%